2007
DOI: 10.1111/j.1095-8339.2007.00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical taxonomy of Juniperus thurifera, J. excelsa and J. foetidissima (Cupressaceae) based on morphological characters

Abstract: Juniperus excelsa and J. thurifera are considered to originate from the same ancestor. As a result of occurring in geographically isolated refuges -J. excelsa in SE Europe and SW Asia and J. thurifera in SW Europe and NW Africa -their divergence could have taken place at the end of the Tertiary, with the climate cooling. Juniperus foetidissima occurs in SE Europe and SW Asia in territories shared with J. excelsa and is similar to and sometimes misidentified with it. The occurrence of the latter two species ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 24 publications
4
34
1
1
Order By: Relevance
“…Average values of particular characters of cone, seed and sprout with leaves of J. thurifera found during study is generally similar to the data reported earlier (do Amaral Franco 1986;Marcysiak et al 2007;Romo and Boratyński 2007), but reveal broader ranges of distribution. The marginal values of particular characters found in our study, taking into account the numbers of tested individuals can, with high probability, be treated as real minima and maxima, while data published earlier resulted from only a few measurements on the herbarium materials (do Amaral Franco 1986) or only few characters (Barbero et al 1994).…”
Section: Evaluation Of Characterssupporting
confidence: 77%
See 2 more Smart Citations
“…Average values of particular characters of cone, seed and sprout with leaves of J. thurifera found during study is generally similar to the data reported earlier (do Amaral Franco 1986;Marcysiak et al 2007;Romo and Boratyński 2007), but reveal broader ranges of distribution. The marginal values of particular characters found in our study, taking into account the numbers of tested individuals can, with high probability, be treated as real minima and maxima, while data published earlier resulted from only a few measurements on the herbarium materials (do Amaral Franco 1986) or only few characters (Barbero et al 1994).…”
Section: Evaluation Of Characterssupporting
confidence: 77%
“…The seeds were taken off the soaked cones and dried after measuring. The thickness of the ultimate lateral branchlet with leaves (ST) was measured following methods described by Marcysiak et al (2007). The measurement was performed on dry material.…”
Section: Plant Materials and Measuring Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphometric traits (e.g. Marcysiak and Mazur, 2007) have been seldom employed. For the first time to the best of the authors' knowledge, this study tackles morphometric variation of needles and cones of J. seravschanica by comparing eight natural Kyrgyz populations.…”
Section: Introductionmentioning
confidence: 99%
“…, Pinus sylvestris L. (Ayan et al 2005;ªevik et al 2010) and Juniperus excelsa Bieb. M. (Barbero et al 1994;Mazur et al 2004;Marcysiak et al 2007;Douaihy et al 2012). Besides, one study of Crimean juniper estimated the amount of genetic variation based on morphological characteristics within and among populations and heritability for a limited number of cone, seed and juvenile seedling characteristics (Yücedað et al 2010), and two studies applied genetic markers to assess genetic diversity within and among populations (Douaihy et al 2011, Douaihy et al 2012Yücedað and Gailing 2013).…”
Section: Vol 70 65-72mentioning
confidence: 99%